ELK4 exerts opposite roles in cytokine/chemokine production and degranulation in activated mast cells - Huang, Yuji; Zhu, Zhehui; Li, Weize; Ge, Yiqin; Li, Yanning; Wang, Juan; Peng, Xia; Lin, Lihui; Li, Jia; Liu, Chen-Ying; Li, Li (Frontiers in Immunology, 2023)
The proliferative potential of mast cells after activation for 3-4h was found to be decreased, which suggests that mast cell degranulation and cell proliferation are differentially regulated. ELK4, a member of the ternary complex factor (TCF) subfamily of Ets transcription factors, is one of the downstream effectors of MAPK signalling that is critical for cell proliferation.And Elk4 has been identified to be vital for macrophage activation in response to zymosan and the transcriptional response to 12-O-tetrade canoyl phorbol-13-acetate (TPA) stimulation in fibroblast. However, the effect of ELK4 on the mast cell transcriptional response to FcεRⅠ and GPCR mediated activation and its potential functional significance in mast cells remain unclear. Here, we showed that ELK4 expression is downregulated in activated mast cells. Elk4 knockout suppresses cell proliferation and impedes the cell cycle in bone marrow-derived mast cells (BMMCs), which is associated with decreased transcription of cell cycle genes. Additionally, the transcriptional activation of cytokines and chemokines is diminished while mast cell degranulation is enhanced in Elk4 knockout BMMCs. Mechanistically, ELK4 might positively modulate Hdc, Ccl3 and Ccl4 transcription by interacting with MITF and negatively regulate the transcription of degranulation-related genes by complexing with SIRT6. Overall, our study identifies a new physiological role of the transcription factor ELK4 in mast cell proliferation and activation.